Notes on the genus Petroplacus (Bacillariophyceae) with new nomenclature transfer - Vishnyakov, Vasily S. (Phytotaxa, 2019)
This paper addresses the taxonomy and biogeography of the recently described diatom genus Petroplacus Pomazkina, Rodionova, Sherbakova & D.M. Williams and relates new information regarding the occurrence of Navicula platystoma var. pantocsekii Wislouch & Kolbe in deep-water benthos of the Rybinsk reservoir, the Upper Volga Region. The variety clearly differs from already established Petroplacus species in valve shape, thus it was transferred to this genus at the specific rank, Petroplacus pantocsekii comb. & stat. nov.